King Bidgood's in the bathtub - Wood, Audrey; Wood, Don 1945-. (San Diego Harcourt Brace Jovanovich, 1985)
Despite pleas from his court, a fun-loving king refuses to get out of his bathtub to rule his kingdom.
Keywords: Children's stories, American; Kings, queens, rulers, etc. -- Fiction; Baths -- Fiction